The theoretical and conceptual framework and application of community empowerment and participation in processes of community development in Malaysia - Abu Samah, Asnarulkhadi; Aref, Fariborz (Marsland Press, 2011)
This study defines and discusses the concept of participation in the context of social development in general, and in terms of community development and community work specifically. Community development could not be achieved without community participation. The principles and techniques underlying the empowering process are also elaborated. The study describes the application of the concepts defined in some of the community work and community development activities in Malaysia.